Kontribusi Modal Kerja Terhadap Likuiditas Pada Perusahaan Daerah Perkreditan Kecamatan di Kabupaten Lebak - Dini Arifian; Ahmad Saepudin; dede suharna; Euis Ajizah (E-Journal Studia Manajemen, 2013)
This study aims to determine the level of liquidity of the District Rural Regional Company (PD, PK) Rangkasbitung influenced by the rotation of working capital. Bank liquidation occurs when a bank is no longer able to meet its short-term obligations to depositors and it can lead to mistrust of the depositors of the bank so that it can reduce the level of the bank's credibility. The method used is quantitative method with a sample balance sheet and profit and loss of the company for 10 years. The results show there is influence between working capital turnover on the level of liquidity in the District Rangkasbitung Credit Local Company.